PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) - Reni Setiawati; Ely Susanti; Avida; Riski Audrilia; Sindi Citra Rahayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study was to improve the learning outcomes of fourth grade mathematics students through the Problem Based Learning (PBL) model. This study is a classroom action research consisting of several stages, namely planning, implementation, observation, and evaluation. The subjects of the study were students of class IV C of SD Negeri 130 Palembang consisting of 16 females and 8 males. The instruments used were written tests and observations. While the observation data were conducted descriptively and qualitatively, the data processing was carried out statistically by examining the implementation of the Problem Based Learning (PBL) learning model and learning outcomes in each cycle. The Minimum Completion Criteria (KKM) that has been set is 65. The learning outcomes of cycle I were 44.7% and the learning outcomes of cycle II were 81.4%. The results of the study showed that the learning outcomes of fourth grade students of class IV C of SD Negeri 130 Palembang can be improved by using the Problem Based Learning (PBL) learning approach. Between cycle I and cycle II, the proportion of students achieving KKM increased from 29% to 79%. Thus, it can be concluded that the learning model is able to improve critical thinking skills and problem-solving skills in mathematics subjects.